Medium-Term Budgetary Frameworks : Lessons for Austria from International Experience - Lundback, Erik. (Washington, D.C. : International Monetary Fund, 2008)
The Austrian government is about to introduce a new fiscal management framework. The first step is to introduce a medium-term budgetary framework, including an expenditure rule. The paper focuses on this first step. The purpose is to describe and evaluate the Austrian model in light of other countries' experiences with their frameworks. An attempt is made to identify features that have proven to be effective elsewhere and that can be applied to the Austrian case. The paper also identifies potential challenges and possible trade-offs when implementing the framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet